Perfil imuno-histoquímico da expressão de ativadores intracelulares com e sem pré-condicionamento com l-alanil-glutamina em modelo de isquemia e reperfusão em cérebros de gerbils - Oliveira, Leidelamar Rosário Alves de (2012)
We investigated the protective effects of L-alanyl-Glutamine (L-ALN-GLN) through the immunohistochemical detection of proinflammatory mediators (IL-6, TNF, NF-kB e HO-1). This was achieved by means of a experimental and controlled study. Fifty-four male gerbils with a mean weight of 150g were used. They were divided randomly and equally into 3 groups: saline with ischemia and reperfusion (SIR), saline without ischemia and reperfusion (SSI) and with L-alanyl-glutamine and with ischemia and reperfusion (GIR). They were then redistributed into three subgroups according to time: T0 (maximum time of ischemia), T30 (30 minutes of reperfusion) and T60 (60 minutes of reperfusion), containing 6 animals each. They were pretreated with saline 2.0mL 0,9% intra-venously (iv) or L-ALN-GLN 0.75% G/KG (IV) 30 min before the start of the experiments. Cerebral ischemia was performed by bilateral occlusion of the common carotid arteries (CCAs) for a period of 15 minutes. After all surgical procedures and at the end of the three time periods the animals were sacrificed and brain tissue samples immediately obtained, which were fixed in 10% formalin solution for 24 hours in order being duly processed prior paraffin embedding. The samples (brain tissue) were collected at the end of each time periods. After this and through using a microtome, tissue sections were made at 4 microns and then placed on glass slides covered with L-polylysine, a proper way for performing immunohistochemistry. The streptavivin-biotin-peroxidase method was used. The quantitative analysis was made by means of counting immunocytochemically-stained cells, both neurons and glial cells, as observed at 400X magnification under an optical microscope Olympus model BX41. Ten fields were observed for each section, with a total of 4 sections per sub-group, always at start, looking for the internal pyramidal layer. Comparing the groups (SSI) and (SIR) a significant increase in NFkB-labeled cells in the subgroup SIR T30 (238,25±218,437 versus 1234,75±144,857); p=0,001 and SIR T60 (586,50±141,210 versus 1286,25±84,968); p=0,002 was observed. There was also a significant increase in the (SIR) subgroup, of the TNF immunostaining at T30 and T60 (263,75±42,906 versus 1015,50±102,796); p=0,01 in comparison to the SSI group. Regarding the cells expressing IL-6 positive labeling, comparing the groups (SIR) and (GIR), it was observed a significant decrease at T30 and T60 in the GIR group (536,25±119,837 versus 9,00±18,000); p=0,033. Comparing the groups (SIR) and (GIR), in relation to the NFkB immunolabeling, there was a significant decrease in group T30 in the GIR group (1234,75±144,857 versus 247,50±495); p=0,001 as well as at T60 (1286,25±84,968 versus 217,75±435,500); p=0,001. There was also a significant decrease, comparing the groups (SIR) and (GIR), of the TNF expression in (GIR) group at all time periods, chiefly at T60 (1015,50±102,796 versus 3,50±7,000); p=0,001. Regarding the immunostaining of the enzyme HO-1, there has been, comparing the groups (SSI) and (SIR), a significant decrease in the expression of this anti-oxidant protein in the SIR group. In the contrary, comparing the groups SIR and GIR, a substantial and significant expression of HO-1 was documented in the group treated previously by the L-alanil-glutamina, at times T30 and T60. In conclusion, the prior administration of L-alanil-glutamina in experiments of ischemia-reperfusion in Gerbils, disclosed a protective outcome, by promoting an in situ reduction in the expression of pro-inflammatory cytokines (TNF and IL-6) and nuclear transcription factor NFkB. At the same time, there has been an increase in the induction of the expression of the anti-oxidative enzyme HO-1, supporting a protective role of this preconditioning agent, chiefly against the inflammatory-oxidative stress. caused by the ischemia reperfusion brain injury model, in Gerbils